The Tradition of Engagement in Traditional Marriage in Pelayangan Sub-District 2012-2022 - Ningrum, Dwie Widya; Wahyuni, Anny; Ramli, Supian (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The tradition of proposing in Jambi Malay wedding customs is an important aspect that reflects social, religious, and cultural norms passed down through generations. In Jambi Malay culture, proposing is not only the initial process leading to marriage but also solidifies relationships between families and the community. This study aims to explain the origins of the proposing tradition, its processes, and the meaning of each stage. The historical research methods used include heuristics, source criticism, interpretation, and historiography. The results of the study show that the proposing tradition in Jambi Malay wedding customs includes various official processes with profound meanings. Based on interviews with traditional leaders, community members, and literature analysis, it was found that this tradition is regulated according to Islamic teachings, as expressed in the Jambi Malay proverb